Development of the Regional Natural Gas Market in Southeast Europe - Emil Asenov (Intereconomics, 2018)
The high level of reliance on external energy supplies, mainly from Russia, is considered a major risk to the energy security in Southeast Europe. This dependency is being addressed by the European Union's new contractual and institutional framework. The construction of new gas pipelines and related infrastructure is being undertaken in a timely manner to secure supplies from alternative energy sources and enhance their sustainability. Still, the EU's policies have run up against Russia's systematic and stubborn resistance as it struggles to preserve its dominance in Europe's energy market and thwart the implementation of competing energy projects. Despite this, Southeast Europe's energy markets will soon be able to ensure a higher level of diversification and secure its supplies.
Keywords: 330